Methanol extract of Iphiona aucheri ameliorates CCl4 induced hepatic injuries by regulation of genes in rats. Issue 6 (14th November 2019) - Zai, Jawaid Ahmed; Khan, Muhammad Rashid; Mughal, Zaib un Nisa; Batool, Riffat; Naz, Irum; Maryam, Sonia; Zahra, Zartash
Graphical Abstract: Abstract: We have investigated the protective potential of methanol extract of Iphiona aucheri (IAM) on the expression of endoplasmic reticulum (ER) stress associated genes and inflammatory genes on carbon tetrachloride (CCl4 ) induced hepatic toxicity in rats. Hepatic damage markers: aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) and bilirubin were elevated while the content of antioxidants: catalase (CAT), superoxide dismutase (SOD), peroxidase (POD) and reduced glutathione (GSH) were decreased significantly ( p < 0.05) in CCl4 treated rats as compared to the control group. The CCl4 intoxication induced a higher expression of glucose-regulated protein 78 kDa (GRP78), X-box-binding protein 1 total (XBP1t), spliced X-box-binding protein 1 (XBP1s), unspliced X-box-binding protein 1 (XBP1u), C/EBP homologous protein (CHOP) and genes involved in inflammation and fibrosis: tumor necrosis factor alpha (TNF-α), transforming growth factor-beta (TGF-β), mothers against DPP homolog 3 (SMAD3), alpha skeletal muscle actin (αSMA) and collagen type I alpha 1 chain (COL1A1). The intoxicated rats showed a low expression of the glutamate–cysteine ligase catalytic subunit (GCLC), protein disulfide isomerase (PDI) and nuclear factor (erythroid-derived 2) like-2 (Nrf2). The administration of IAM to intoxicated rats restored the expression of ER stress, inflammatory, fibrosis and antioxidant genes in a dose dependent manner. Our results indicated that IAM can impede the ER stress and inflammatory genes and it could be a complementary and alternative therapeutic agent for oxidative stress associated disorders.